Dietary aspects of establishing a mainland-based colony of the endangered African Penguin (Spheniscus demersus) in St Francis Bay, South Africa - Voogt, Nina Margaret (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Cape St Francis, Eastern Cape, has been identified as one of four potential sites for establishing a mainland-based African penguin (Spheniscus demersus) colony. This thesis comprises three main components: a verification of a preparation method for stable isotope samples from penguin feathers; a dietary analysis of the penguins on Bird Island, Algoa Bay, though stable isotope analysis of whole blood and feathers (2012 and 2013); and an estimation of available fish surplus that could potentially support a colony of penguins at Cape St Francis. Each component contributes towards the next, all building towards answering the main research question: Will there be enough food around St Francis Bay to support a colony of penguins and sustain the already established fisheries industry within the bay? Stable isotope analysis of whole blood and feathers from breeding adults and whole blood from juveniles provided insight into the variability of African penguins' diets at different stages in their life history. Stable isotope mixing models indicated that the predicted proportions that each prey species could potentially contribute to diet conflicted with published stomach sample data. This might arise from inaccurate trophic enrichment factors used in the model, or from systematic biases in the published stomach sampling techniques, or both. Dietary sexual dimorphism was not demonstrated by the isotope signatures of breeding penguins. Based on official catch data, the fisheries activity on the south coast, and especially around the potential colony site at St Francis, is much lower than around the west coast's penguin colonies. The model provided a first-order estimate for fish supply around the potential colony site at St Francis both at a large coastal scale and a local small scale. At both scales the estimate indicated an ample availability of fish at current fishing levels. The model in Chapter 4 can also be applied to refining the assessments of other potential colony sites on the south coast. In conclusion, the south coast is a promising area for a new colony of penguins in terms of food availability. There is relatively low fishing activity in the area and, as suggested by the large-scale model in Chapter 4, an ample fish resource. The final chapter briefly discusses factors that need to be considered before attempting to establish a mainland-based colony of African penguins.
Keywords: African penguin -- South Africa -- Cape Saint Francis; African penguin -- Food -- South Africa -- Algoa Bay; African penguin -- Habitat suitability index models -- South Africa -- Cape Saint Francis; Stable isotopes